FX intervention in the yen-US dollar market: A coordination channel perspective - Stefan Reitz; Mark P. Taylor (Kiel Institute for the World Economy (IfW), 2012)
The coordination channel has recently been established as an additional means by which foreign exchange market intervention may be effective. It is conjectured that strong and persistent misalignments of the exchange rate are caused by a coordination failure among fundamentals-based traders. In such situations official intervention may act as a coordinating signal, encouraging traders to engage in stabilizing speculation. We apply the framework developed in Reitz and Taylor (2008) to daily data on the yen-US dollar exchange rate and on Federal Reserve and Japanese Ministry of Finance intervention operations. The results provide further support for the coordination channel of intervention effectiveness.
Keywords: C10; F31; F41; 330; foreign exchange intervention; coordination channel; STR-GARCH model